Error reduction in trauma care: Lessons from an anonymized, national, multicenter mortality reporting system. Issue 3 (March 2022) - Hamad, Doulia M.; Mandell, Samuel P.; Stewart, Ronald M.; Patel, Bhavin; Guttman, Matthew P.; Williams, Phillip; Thomas, Arielle; Jerath, Angela; Bulger, Eileen M.; Nathens, Avery B.
Abstract : BACKGROUND: Twenty years ago, the landmark report To Err Is Human illustrated the importance of system-level solutions, in contrast to person-level interventions, to assure patient safety. Nevertheless, rates of preventable deaths, particularly in trauma care, have not materially changed. The American College of Surgeons Trauma Quality Improvement Program developed a voluntary Mortality Reporting System to better understand the underlying causes of preventable trauma deaths and the strategies used by centers to prevent future deaths. The objective of this work is to describe the factors contributing to potentially preventable deaths after injury and to evaluate the effectiveness of strategies identified by trauma centers to mitigate future harm, as reported in the Mortality Reporting System. METHODS: An anonymous structured web-based reporting template based on the Joint Commission on Accreditation of Healthcare Organizations taxonomy was made available to trauma centers participating in the Trauma Quality Improvement Program to allow for reporting of deaths that were potentially preventable. Contributing factors leading to death were evaluated. The effectiveness of mitigating strategies was assessed using a validated framework and mapped to tiers of effectiveness ranging from person-focused to system-oriented interventions. RESULTS: Over a 2-year period, 395 deaths were reviewed. Of the mortalities, 33.7% were unanticipated. Errors pertained to management (50.9%), clinical performance (54.7%), and communication (56.2%). Human failures were cited in 61% of cases. Person-focused strategies like education were common (56.0%), while more effective system-based strategies were seldom used. In 7.3% of cases, centers could not identify a specific strategy to prevent future harm. CONCLUSION: Most strategies to reduce errors in trauma centers focus on changing the performance of providers rather than system-level interventions such as automation, standardization, and fail-safe approaches. Centers require additional support to develop more effective mitigations that will prevent recurrent errors and patient harm. LEVEL OF EVIDENCE: Therapeutic/Care Management, level V. Abstract : "Lessons from 395 deaths with an opportunity for improvement in trauma: centers continue to focus on improving people, not systems. System-level strategies (standardization, automation, etc.) could help prevent recurrent errors and patient harm.#trauma #quality #errorprevention"Supplemental digital content is available in the text.